تجليات الذات المتكلمة في مناظرات القرآن الكريم - Ouahiba Khabil (Al-Lisaniyyat)
The topics of the debates are based on the consideration that they are an oral discourse in the process of pronouncing words in a deliberative manner between the presenter and the objector, so that the plurality of the subject voices expresses their entities and roles in the text. This phenomenon, specific to verbal interaction, is what inspired us to address the issue of the polyphony of the subject voices in some models of the debates of the Holy Qur’an (the debates of Noah, Abraham and Moses, peace be upon them), given that verbal interaction in its most complete forms and its most eloquent objectives is found in the Holy Qur’an, which is a unique model in the meaning and construction that humanity refers to. In our study, we have exploited the "integrated deliberative" theses that focus on the speaker and the characteristic of "plurality" inherent in interactive discourse in an apparent or implicit manner, so that it is divided into self-production and receptivity on the one hand, and argumentation and controversy on the other hand.